THE INFLUENCE OF NUTRITIONAL STATUS ON THE LEVEL OF INTELLIGENCE IN ELEMENTARY-SCHOOL CHILDREN - Kristanti, Melly; Nugrohowati, Nunuk; Chairani, Aulia; Kita, Bungahati; Aritha Rebecca Ayu Sibarani (Universitas Airlangga, 2025)
Introduction: Intelligence level is a person's ability to think and respond to things logically, purposefully, and to control and manage the environment more effectively. Nutritional status and parenting of children affect the level of child's carelessness. Basic Health Research (Riskesdas) 2018 showed the nutritional status of children aged 5-12 years, where 26.8% were anemic (children aged 5-14 years), 23.6% were short, 10.8% were fat, 9.2% were think, and 9.2% were obese. Aims: The researcher hopes to determine how parenting and nutritional status affect elementary school students' Intelligence Quotient (IQ). Methods: Purposive sampling strategies are used in this cross-sectional study design. The number of samples in this study is 77 samples. Results: The result found the effect of nutritional status on children's intelligence level (p=0.006; OR 95% CI 4.17 (1.51-11.52) vs Parenting with intelligence level (p=0.343; OR 95% CI 1.35 (0.72-2.54). Nutritional status is something that greatly affects the development of a child's brain so that it can be ensured that good nutritional intake can increase the level of intelligence of children. Conclusion: Therefore, it is necessary to increase counseling programs and also continue existing government programs, such as counseling for mothers or parents related to balanced nutrition, providing counseling on making balanced nutritional foods, increasing the budget in providing supplementary feeding that contains high protein, and hence, the Sustainable Development Goals (SDGs) program to reduce the malnutrition rate can be achieved in order to create healthy and intelligent children for the nation's successors.